2018
DOI: 10.5688/ajpe6190
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of the Pharmacist’s Approach Across the Varying Levels of Medication Therapy Management Services

Abstract: Objective. To explore third-year pharmacy (P3) student perceptions of medication therapy management (MTM) after an introduction to the various levels of MTM services within an MTM course. Methods. A qualitative survey was conducted of 158 P3 students. Open-ended questions were used to explore students' thoughts, feelings, and perceptions related to the pharmacist's approach in MTM following a lecture establishing differences in roles and responsibilities between the varying levels of MTM. Emphasis was placed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, since that time, payors, legislators, academics, professional organizations, and practitioners have added complexity to the concept of MTM. Such ambiguity surrounding MTM terminology [17–19] and continued debate surrounding what constitutes MTM [1820] may be directly and negatively impacting MTM implementation and setting-specific adaptation. In an attempt to alleviate this issue, the pharmacy profession established Core Elements for MTM services: medication therapy review (MTR), personalized medication record (PMR), medication action plan (MAP), intervention and/or referral, and documentation and follow-up [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, since that time, payors, legislators, academics, professional organizations, and practitioners have added complexity to the concept of MTM. Such ambiguity surrounding MTM terminology [17–19] and continued debate surrounding what constitutes MTM [1820] may be directly and negatively impacting MTM implementation and setting-specific adaptation. In an attempt to alleviate this issue, the pharmacy profession established Core Elements for MTM services: medication therapy review (MTR), personalized medication record (PMR), medication action plan (MAP), intervention and/or referral, and documentation and follow-up [12].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers believe this inconsistent MTM implementation stems from inconsistent definitions of MTM, lack of clarity regarding the core components of MTM, and lack of implementation support to assist pharmacists with adapting MTM. 10,11 Previous research has shown that recommendations from a health professional increase the likelihood that patients will comply with recommended medication protocols. 8,12 Because patients interact more frequently with community health professionals, they are able to play a significant role in ensuring that these patients receive effective medication therapy so that they can successfully manage their diabetes and hypertension.…”
Section: Introductionmentioning
confidence: 99%